Assessment of the variability of unidirectional prepregs at multiple scales - Silvia Gomarasca; S. M. A. Hossein; Ran Tao; Benedikt Boos; Christoph Queck; Daniel Peeters; Bilim Atli-veltin; Martin Gurka; Clemens Dransfeld (e-Journal of Nondestructive Testing)
Understanding the microstructural variability in unidirectional composite prepreg tapes is relevant to investigating mechanisms of tape microstructure formation, their impact on its processability and the mechanical performance of the final composite part. It has been shown that three-dimensional microstructural variability at the single-fibre level can be resolved by X-ray micro-computed tomography (XCT). However, to define a representative microstructural fingerprint of a given tape, investigations at the required small voxel size lead to limited volumes of observation, which might not be representative. This research aims to extend these findings via a multiscale approach, considering scales of observations, from microscopic (single fibre) up to mesoscopic (dimension of tape) length scale, to generate further insight into the microstructural organisation of thermoplastic prepreg tapes. By exploring the ability of XCT imaging for carbon fibre-reinforced thermoplastic composites at different voxel sizes, the work aims to identify the limitations of the use of different scales of observations to capture features of microstructures and their propagation from micro- to mesoscale level. While structure tensor analysis appeared to correctly capture misaligned regions in XCT images with small voxel size (1/10 of the fibre diameter), the method proved ineffective for larger voxel size images (1/2 of the fibre diameter).